Learning Arabic with Al-Thariqah Al-Mubasyarah - Sukri Ilahi (Penerbit Hellow Pustaka, 2025)
Al-Tariqah al-mubasyarah (direct method) is the most widely used and well-known method. However, this method also causes a lot of controversy. This method is used in Berlizt schools. Therefore, some people call this method the Berlitz method. The characteristics of the direct method are 1). The lesson material consists of words and sentence structures that are commonly used in daily life. 2). Grammar is taught through situations and done orally, not by memorizing grammar rules. Grammar is taught through situations and done orally, not by memorizing grammar rules. In principle, this direct method is very important in foreign language teaching, because through this method, students can directly practice their speaking skills without using their mother tongue (the language of their environment), even though at first it may seem difficult for students to imitate. The emphasis of this method is on continuous conversation practice between the teacher and the students using Arabic without any use of the mother tongue, whether in explaining the meaning of vocabulary or in translation.